Predicting exercise behavior: Testing personal, athletic, and psychological variables - Gomes, A. R.; Capelão, T. (International Journal of Sports Science, 2012)
This study analyzes whether personal, athletic, and psychological factors predict the perception of current exercise frequency. The study included 193 participants, of whom 130 were females (67.4%) and 63 were males (32.6%). Personal and athletic information, current exercise frequency, exercise attitudes, perceived behavioral control, expected outcomes of exercising, behavioral regulation, satisfaction with life, and satisfaction with body shape and physical appearancewere evaluated. The results showed that perception of current exercise frequency was best predicted by personal and athletic variables, followed by satisfaction with body shape and physical appearance, intrinsic regulation, and negative expectations about exercise. In conclusion, considering the role of personal and athletic variables (and some psychological dimensions) seems important in explaining exercise behavior.